The persistent consequences of civil conflict: Evidence from a new measure for subnational conflict exposure - Tobias Korn (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2023)
This paper presents a novel approach to accounting for subnational conflict exposure and provides new insights into the causal medium-run effects of conflict on economic development. The existing literature has not reached a consensus on whether civil conflict can permanently alter economic growth trajectories. This study identifies the source of this disagreement as differing methodologies in measuring conflict exposure. Commonly, researchers rely on subnational aggregates of conflict intensity, overlooking crucial intra-regional variation. To provide a more accurate assessment, this paper proposes measuring conflict exposure as the share of economic activity in proximity to conflict events. Estimating a Bartik-like IV model at the district level across 70 countries, I provide causal evidence that conflict exposure significantly decreases economic activity in the medium run. As potential channels, I identify persistent diversions of investments and human capital.
Keywords: D74; O15; O43; 330; civil conflict; conflict exposure; economic development; Bartik IV